From genomic databases to translation: a call to action. Issue 8 (26th May 2011) - Knoppers, Bartha Maria; Harris, Jennifer R; Burton, Paul R; Murtagh, Madeleine; Cox, David; Deschênes, Mylène; Fortier, Isabel; Hudson, Thomas J; Kaye, Jane; Lindpaintner, Klaus
Abstract : The rapid rise of international collaborative science has enabled access to genomic data. In this article, it is argued that to move beyond mapping genomic variation to understanding its role in complex disease aetiology and treatment will require extending data sharing for the purposes of clinical research translation and implementation.